PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI BALAI KONSERVASI TUMBUHAN KEBUN RAYA EKA KARYA BALI - Ni Nyoman Lidyantari; I Wayan Arta Artana; IGAB Widiantara (Universitas Triatma Mulya, 2021)
An organization manage HR with disciplined attitudes and behavior. Employee discipline can have a strong impact on an organization to achieve success. This study aims to determine the effect of compensation and work discipline partially on employee performance at the